(untitled) (Research, Society and Development, 2020)
The objective of this qualitative study was to analyze conceptions and assessment practices of learning in high school technical courses at the IFCE Caucaia Campus. The methodological field is based on the qualitative approach In the methodological field, the case study was used, as well as the application of questionnaires and interviews with students and teachers. Bibliographic and documentary research were also used for the theoretical basis and exploration of the theme. For the discussion and analysis of the data, the Content Analysis method was adopted. The main results indicate that, in the teaching routines, diversified assessment strategies are introduced. However, despite these strategies, there has not yet been a break with traditional models, effecting changes towards a diagnostic and formative assessment proposal that may supplant the selective, exam focused and content-oriented conception and that may highlight the democratization of the high school technical education.